Assessment of Low-Impact development for managing aquatic ecosystem - Sa'd Shannak (17191363) (2021)
Urban aquatic life communities are among the most endangered species in the United States, and their decline has been linked to pollutants and sediments from urban development. Low Impact Development (LID) practices were applied to manage urban stormwater runoff as part of green infrastructure. However, there remains a debate regarding the role played by LIDs in protecting aquatic life due to a lack of large-scale evidence. Given this knowledge gap, a Sub-hourly time step SWAT (Soil Water Assessment Tool) model was calibrated and validated to evaluate the potential impact of LID practices on aquatic life in the Blunn Creek Watershed in Austin-Texas. The evaluation of LID practices performance was based on (i) incorporating and representing these practices into the SWAT model, (ii) studying output flows, and (iii) assessing watershed hydrological responses and their impact on aquatic life communities. Several measures such as reduction in peak flows, increasing both baseflows, and Aquatic Life Potential (AQP) values were used to assess flows coming out of LID practices. The types of LIDs considered were raingarden, permeable pavement and detention pond. Results showed that a combination of permeable pavement and raingarden resulted in the greatest percentage of increase in AQP values and baseflows and the greatest reduction in peak flows. The detention pond had the least percentage increase in AQP and baseflows as well as the least percentage of reduction in peak flows. The findings of this study are likely to be of interest to policymakers. LIDs are efficient applications on a watershed scale and could contribute to reduce total runoff and enhance outflow water quality. This study provides an in-depth discussion over the latest essence of LID technologies, which magnify their capabilities to control stormwater, while also protecting urban aquatic life. Cities and developers should encourage the development of green cities using LID technologies. Other Information Published in: Ecological Indicators License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ecolind.2021.108235